Priority to Organ Donors: Personal Responsibility, Equal Access and the Priority Rule in Organ Procurement (Diametros, 2017)
In the effort to address the persistent organ shortage it is sometimes suggested that we should incentivize people to sign up as organ donors. One way of doing so is to give priority in the allocation of organs to those who are themselves registered as donors. Israel introduced such a scheme recently and the preliminary reports indicate increased donation rates. How should we evaluate such initiatives from an ethical perspective? Luck egalitarianism, a responsibility-sensitive approach to distributive justice, provides one possible justification: Those who decide against being organ donors limit the health care resources available to others. As such, a priority rule can be justified by a luck egalitarian approach to distributive justice. Furthermore, a priority rule inspired by luck egalitarianism is well equipped to avoid prominent criticisms of such a procurement system. Luck egalitarianism provides us with reaons to exempt people who are not responsible for their inability to donate from receiving lower priority, provide sufficient information about donation, and mitigate social and natural circumstances affecting people’s choice to donate.
Keywords: organ shortage; priority rule; priority to organ donors; luck egalitarianism; personal responsibility; reciprocity; club model; incentive to organ donation; equal access; Israel; organ donation; organ transplantation; distributive justice